Gastroprotective Effects of Periplaneta americana L. Extract Against Ethanol-Induced Gastric Ulcer in Mice by Suppressing Apoptosis-Related Pathways - Fu, Shu; Chen, Jiamei; Zhang, Chen; Shi, Jinfeng; Nie, Xin; Hu, Yichen; Fu, Chaomei; Li, Xiaofang; Zhang, Jinming (Frontiers in Pharmacology, 2021)
Although Periplaneta americana L. and its modern preparation, Kangfuxin liquid, have been extensively applied for ulcerative diseases in gastrointestinal tract (e.g., gastric ulcer (GU) and ulcerative colitis, the effective components and potential mechanisms) remain unclear. In accordance with the accumulating research evidences, the relieving/exacerbating of GU is noticeably correlated to focal tissue programmed cell death. Herein, gastro-protective effects of the effective Periplaneta americana L. extract (PAE) fraction were assessed in vitro and in vivo, involving in programmed cell death-related signaling channels. To screen the effective PAE fraction exerting gastroprotective effects, several PAE fractions were gained based on a wide range of ethanol solution concentration, and they were assessed on ethanol-induced ulcer mice. Based on HPLC investigation with the use of nucleosides, the chemical composition of screened effective PAE, extracted by 20% ethanol, was analyzed in terms of quality control. Based on CCK-8 assay, the protective effects on GES-1 cells, impaired by ethanol, of PAE were assessed. After 3 day pre-treatment with PAE (200, 400, 800 mg/kg), the gastric lesions were assessed by tissue morphology, and periodic acid-schiff (PAS) staining, as well as hematoxylin and eosin (H&E) based histopathology-related investigation. The levels for inflammation cytokines (IL1-β, TNF-α, IL-18, PGE2 and IL-6), antioxidant indices (SOD and MDA) were examined via ELISA. In the meantime, based on Western Blotting assay, the expression levels of some programmed cell death-related protein targets (NLRP3, caspase-1, NF-κB p65, MyD88, and TLR4) were analyzed. As revealed from the results, PAE is capable of alleviating gastric mucosa impairment, suppressing the inflammatory cytokines, and down-regulating the MyD88/NF-κB channels. Accordingly, 20% ethanol extract of Periplaneta americana L. would contribute its gastroprotective effects, thereby providing the evidence that its anti-GU mechanisms correlated with inhibiting programmed cell death channel.